15.0k views
4 votes
4x−3/2 − 5−2x/3 − 3x−4/3 = 5

User Bjorgum
by
5.5k points

1 Answer

3 votes

Answer:

Explanation:

4x - 3/2 - 5 - 2x/3 - 3x - 4/3 = 5

Give all terms least common denominator of 6:

4x(6/6) - 3/2(3/3) - 5(6/6) - 2x/3(2/2) - 3x( 6/6)- 4/3(2/2) = 5(6/6)

24x/6 - 9/6 - 30/6 - 4x/6 - 18x/6 - 8/6 = 30/6

Combine x terms and numerical terms:

2x/6 - 47/6 = 30/6

2x/6 = 77/6 (Add 47/6)

2x = 77 (Multiply both sides by 6)

x = 77/2 = 38.5

User Anoop Vaidya
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.